KISAH DALAM AL-QURAN - Amin, Arwani (Dirasat: Journal Islamic Studies, 2024)
This research aims to explore the urgency of the stories in the Al-Qur'an, their benefits and educational influence. To make this happen, researchers used inductive and analytical methods by tracing the verses of the Koran and analyzing them, supported by what their predecessors had written. This research has come to the conclusion that the story in the Qur'an is important because Allah Himself revealed it, ordered His prophet to tell it, it is the best story, and it is the real embodiment of a value. The stories in the Koran have a number of great benefits. Namely, strengthening the heart, confirming the truth of the message, and that it comes from Allah, establishing the pillars of religion, being ibrah and to straighten one's morals. As the stories in the Koran also have a very deep educational influence. Namely, broadening the scope of insight, forming a spirit of imitation, ensuring that a value can be realized, knowing the reasons for the progress and destruction of nations, and upgrading tastes.